2013
DOI: 10.1152/ajprenal.00011.2012
|View full text |Cite
|
Sign up to set email alerts
|

Sensory renal innervation: a kidney-specific firing activity due to a unique expression pattern of voltage-gated sodium channels?

Abstract: Freisinger W, Schatz J, Ditting T, Lampert A, Heinlein S, Lale N, Schmieder R, Veelken R. Sensory renal innervation: a kidney-specific firing activity due to a unique expression pattern of voltage-gated sodium channels? Am J Physiol Renal Physiol 304: F491-F497, 2013. First published January 2, 2013; doi:10.1152/ajprenal.00011.2012.-Sensory neurons with afferent axons from the kidney are extraordinary in their response to electrical stimulation. More than 50% exhibit a tonic firing pattern, i.e., sustained act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…For instance, renal neurons exhibited sustained action potential (AP) firing upon stimulation with depolarizing current injections (tonic response pattern). We also showed that this firing pattern was related to an increased expression of specific subgroups of voltage-gated sodium channels, namely Nav1.7, Nav1.8, and Nav1.9 (13). Expression of voltage-gated sodium channels is sensitive to inflammatory conditions.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…For instance, renal neurons exhibited sustained action potential (AP) firing upon stimulation with depolarizing current injections (tonic response pattern). We also showed that this firing pattern was related to an increased expression of specific subgroups of voltage-gated sodium channels, namely Nav1.7, Nav1.8, and Nav1.9 (13). Expression of voltage-gated sodium channels is sensitive to inflammatory conditions.…”
mentioning
confidence: 67%
“…Therefore, we hypothesized that inflammatory chemokines (6, 37) alter neuro-and electrophysiological properties of renal afferent nerves. We previously established an in vitro model of renal sensory afferent nerves by cultivating respective dorsal root ganglion (DRG) neurons in primary cell culture (10,13) to investigate neuronal mechanisms that cannot be tested by single or multifiber recording in vivo (15,41). We demonstrated that neurons with afferent axon projections to the kidney were distinctively different from neurons with axon projections to other sites (10).…”
mentioning
confidence: 99%
“…In some cases, authors have adopted the same criteria described above for sympathetic neurons (e.g., Ditting et al 2009;Yu et al 2014). Other authors used a more strict criteria for phasic neurons based on the number of APs fired during a continuous suprathreshold simulation, with phasic neurons firing exactly one (Chen et al 1987) or, at most, four APs (Sculptoreanu and de Groat 2007;Freisinger et al 2013). Neurons that fired more than these limits were classified as tonic cells.…”
Section: Action Potential Firing Patternsmentioning
confidence: 99%
“…For example, 90% of DRG neurons innervating the bladder are phasic (Kanda et al 2016), and capsaicin-sensitive bladder afferents change their firing pattern from phasic to tonic after spinal transection (Takahashi et al 2013). Similarly, Freisinger et al (2013) showed that a higher percentage of renal afferents are tonic (56%) compared to nonrenal afferents (12%). In mechanosensitive DRG neurons, neurons with Bnociceptive-like^APs were equally likely to have tonic or phasic responses, while neurons with Bnonnociceptive-like^APs are almost all phasic (ViatchenkoKarpinski and Gu 2016).…”
Section: Functional Relationships Associated With Tonic and Phasic Fimentioning
confidence: 99%
See 1 more Smart Citation